2018
DOI: 10.1021/acscatal.8b03802
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Fe–N/C Hybrid for Enhanced Nitrogen Reduction Electrocatalysis under Ambient Conditions in Aqueous Solution

Abstract: Developing efficient noble-metal-free catalysts for the electrochemical N 2 reduction reaction (NRR) under ambient conditions shows promise in fertilizer production and hydrogen storage. Here, as a proof-of-concept prototype, we design and implement an Fe−N/C−carbon nanotube (CNT) catalyst derived from a metal−organic framework and carbon-nanotube-based composite with built-in Fe−N 3 active sites. This catalyst exhibits enhanced NRR activity with NH 3 production (34.83 μg•h −1 •mg −1 cat. ), faradaic efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
199
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(210 citation statements)
references
References 75 publications
11
199
0
Order By: Relevance
“…PGM‐free SACs, including Mo and Fe based electrocatalysts, have also been studied for the NRR. In particular, the FeN 4 catalyst exhibited an NH 3 yield rate of 62.9 ± 2.7 µg h −1 mg−1 cat.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis Formentioning
confidence: 99%
“…PGM‐free SACs, including Mo and Fe based electrocatalysts, have also been studied for the NRR. In particular, the FeN 4 catalyst exhibited an NH 3 yield rate of 62.9 ± 2.7 µg h −1 mg−1 cat.…”
Section: Atomically Dispersed Single Metal Site Electrocatalysis Formentioning
confidence: 99%
“…Based on N 2 temperature‐programmed desorption and DFT calculation, the author revealed that the coordination of Ru with N atom can enhance the adsorption energy for N 2 molecule, thus improving the reaction activity. Except the noble‐atom SACs, the Mo and Fe based SACs have recently been studied for electrocatalytic NRR and exhibit competitive activities.…”
Section: Electrocatalytic Performancementioning
confidence: 99%
“…A typical example is the metal–organic framework compound‐carbon nanotube (MOF‐CNT)‐derived Fe−N/C electrocatalyst. When NRR took place on Fe−N/C with built‐in Fe−N 3 active sites, all of the features, including the hierarchically porous architecture together with large surface area, positively charged surface, and weak ferromagnetism, contributed to NRR activity . Computational study of single‐atom Fe revealed that increasing the magnetic moment strengthened the adsorption of dinitrogen and promoted charge transfer from graphene substrate to the adsorbed dinitrogen molecule .…”
Section: Design Principles For Electrocatalystsmentioning
confidence: 99%